9u-u=

Simple and best practice solution for 9u-u= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9u-u= equation:


Simplifying
9u + -1u = 0

Combine like terms: 9u + -1u = 8u
8u = 0

Solving
8u = 0

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Divide each side by '8'.
u = 0

Simplifying
u = 0

See similar equations:

| 18t=6+6(4t+11) | | y-4.73=7.4 | | r-9.2=-6.8 | | 5x^2-3x+4=x^2-3x+13 | | (x+5)/4=7 | | c+20=15 | | 42=2w+8 | | k(2)+2k-71=9 | | d/20=9 | | k/4=-15 | | Xy-5y-2x+10= | | -6w=108 | | 8x^3y^2+27y^2= | | 6x-30=x-x+4 | | n-20=-19 | | 14x^2-5=0 | | -7+ln(3x)=4 | | 5x^2y^3(3x^2+xy+4y)= | | (s+2)+2s=8 | | -120x+3000=1500 | | -160x+4000=2500 | | 10y-15=0 | | 7x+1-3x-8= | | (X^2-xy+y^2)(x+y)= | | -120x+3000=2500 | | r/4-12=-14 | | 12x^2+x-13=-7 | | -14.875+15+1/3 | | 6x+4=4x+20 | | -12+10z=-30 | | -12c-12=-24 | | 5x-2(3x+4)=-11 |

Equations solver categories